Management of perioperative low cardiac output state without extracorporeal life support: What is feasible? - Kumar Girish; Iyer Parvathi (Wolters Kluwer Medknow Publications, 2010)
A transient and reversible reduction in cardiac output-low cardiac output state (LCOS) often occurs following surgery for congenital heart disease. Inappropriately managed LCOS is a risk factor for increased morbidity and death. LCOS may occasionally be progressive and refractory needing a period of "myocardial rest" with extracorporeal life support (ECLS). ECLS is currently considered a routine tool available for rapid deployment in most industrialized countries. Accumulated experience and refinements in technology have led to improving survivals - discharge survivals of 35%−50%, with almost 100% survival in select groups on elective left ventricular assist device. Thus, there is an increasing trend to initiate ECLS "early or electively in the operating room" in high-risk patients. India has a huge potential need for ECLS given the large number of infants presenting late with preexisting ventricular dysfunction or in circulatory collapse. ECLS is an expensive and resource consuming treatment modality and is not a viable therapeutic option in our country. The purpose of this paper is to reiterate an anticipatory, proactive approach to LCOS: (1) methods for early detection of evolving LCOS and (2) timely initiation of individualized therapy. This paper also explores what is feasible with the refinement of "simple, conventional, inexpensive strategies" for the management of LCOS. Therapy for LCOS should be multimodal based on the type of circulation and physiology. Our approach to LCOS includes: (1) intraoperative strategies, (2) aggressive afterload reduction, (3) lusitropy, (4) exclusion of structural defects, (5) harnessing cardiopulmonary interactions, and (6) addressing metabolic and endocrine abnormalities. We have achieved a discharge survival rate of greater than 97% with these simple methods.